Analysis of the Dissolution Mechanism of Drugs into Polymers: The Case of the PVP/Sulindac System - Mansour Latreche; Jean-François Willart (MDPI AG, 2023)
This paper is dealing with the dissolution mechanism of crystalline sulindac into amorphous Polyvinylpyrrolidone (PVP) upon heating and annealing at high temperatures. Special attention is paid on the diffusion mechanism of drug molecules in the polymer which leads to a homogeneous amorphous solid dispersion of the two components. The results show that isothermal dissolution proceeds through the growth of polymer zones saturated by the drug, and not by a progressive increase in the uniform drug concentration in the whole polymer matrix. The investigations also show the exceptional ability of temperature Modulated Differential Scanning Calorimetry (MDSC) to identify the equilibrium and out of equilibrium stages of dissolution corresponding to the trajectory of the mixture into its state diagram.